IMF Staff papers : Volume 31 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1984)
This paper analyzes the efficacy of alternative financial stabilization policies in response to disturbances from various sources. A model, appropriate to the institutional structure of a developing country, is estimated. The model is subjected to shocks from the domestic real economy, domestic financial circumstances, and the external terms of trade. Alternative policy reactions are evaluated with respect to each of these shocks. A few generalizations may be drawn from the results. First, exchange rate changes are a powerful instrument of adjustment, even when the estimated price elasticities of trade are small. Second, even in a country that does not have an open financial system that is integrated with the rest of the world, monetary conditions have a large and rapid effect on the balance of payments. The appropriate policy response to any disturbance depends on the expected duration of the disturbance. The benefits of avoiding excessive early adjustment must be weighed against the costs of a probable greater and more painful, adjustment at a later stage.